Post-manifesto polygamy : the 1899-1904 correspondence of Helen, Owen, and Avery Woodruff - Snyder, Lu Ann Faylor; Snyder, Phillip A. (Life writings of frontier women, 2009)
"These letters among two women and their husband offer a rare look into the personal dynamics of an LDS polygamous relationship. Abraham "Owen" Woodruff was a young polygamous Mormon apostle, and the son of LDS President Wilford Woodruff, who is remembered for the Woodruff Manifesto, a divinely-inspired call for the termination of plural marriage. The Woodruff Manifesto eased a systematic federal judicial assault on Mormons and made Utah statehood possible. It did not end polygamy in the church. Some leaders continued to encourage and perform such marriages. Owen Woodruff, himself married to Helen May Winters, contracted a secretive second marriage to Avery Clark. Pressure on the LDS church revived with hearings regarding Reed Smoot's seat in the U.S. Senate. After church president Joseph F. Smith issued the so-called Second Manifesto in 1904, polygamy and its more prominent advocates were mostly expunged from mainstream Mormonism. Owen Woodruff had often been "on the underground," moving frequently, traveling under secret identities, and using code names in his letters to his wives, while still carrying out his administrative duties, which, in particular, involved supervision of the nascent Mormon colonies in the Big Horn Basin of Wyoming. He was never excommunicated, as some of his apostolic colleagues were. Both he and his first wife, Helen, while living with Avery in Mexico and preparing for a mission to Germany, contracted smallpox and died suddenly in 1904. Avery later returned to Utah with her children along with those of Helen and Owen."--Publisher's description